RETRACTED: Emodin Interferes With AKT1-Mediated DNA Damage and Decreases Resistance of Breast Cancer Cells to Doxorubicin - Li, Bo; Zhao, Xin; Zhang, Lei; Cheng, Wen (Frontiers in Oncology, 2021)
Doxorubicin is a cytotoxic drug used for the treatment of breast cancer (BC). However, the rapid emergence of resistance towards doxorubicin threatens its clinical application, thus the need for combination therapy. Here, we interrogate the role of Emodin, a chemical compound with tumor inhibitory properties, in the resistance of BC to Doxorubicin. We first evaluated the efficacy of Emodin in the treatment of BC cells. We then used γH2A to examine doxorubicin-induced DNA damage in BC cells, with or without Emodin. Data from CCK-8, flow cytometry and tumor xenograft assays showed that Emodin suppresses the growth of BC cells. Further, we demonstrated that Emodin enhances γH2A levels in BC cells. Moreover, bioinformatics analysis and western blot assays indicated that Emodin down-regulates the AKT1 expression, and marginally decreases the levels of DNA damage repair proteins (XRCC1, PARP1, and RAD51) in BC cells. Taken together, our data demonstrates that Emodin affects cell proliferation, and DNA damage repair pathways in BC cells, thus increasing the sensitivity of BC cells to doxorubicin. Besides, we confirmed that Emodin confers sensitization of BC to doxorubicin through AKT1-mediated DNA repair.